Bigger Is Not Always Better: The Effect of Obesity on Sexual Satisfaction and Behavior of Adult Men in the United States. (October 2013) - Carr, Deborah; Murphy, Lauren F.; Batson, Heather D.; Springer, Kristen W.
We use data from the Midlife Development in the United States study to examine how sexual satisfaction, frequency, and number of partners are associated with men's body weight. We consider five body weight categories (underweight, normal, overweight, obese I, and obese II/III), and control for potential explanatory factors including demographic characteristics, socioeconomic status, health, perceived stigmatization, and adolescent weight. Obese II/III men report significantly less sexual satisfaction and less frequent sexual activity, and a greater likelihood of having no sex partner compared to normal weight men. Physical and mental health conditions partially account for obese II/III men's less satisfying and less frequent sex. However, the deleterious effects of obesity are suppressed by youthful weight. Obese II/III men are more likely to have been overweight adolescents, an attribute associated with more frequent and satisfying sex in adulthood. We discuss implications for the study of masculinities, and the ways that bodies and their symbolic meanings can shape men's sexual lives.